2006
DOI: 10.1182/blood-2006-07-033159
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection and pathogenesis in a novel humanized mouse model

Abstract: IntroductionThe hallmarks of AIDS are high levels of HIV-1 infection, depletion of CD4 ϩ T cells, and loss of immunity. The mechanism of HIV-1 immunopathogenesis is not clear because human patients are the only hosts that support high levels of HIV-1 replication and develop AIDS. Extensive studies have been performed in primate models with either low levels of HIV-1 replication (HIV-1 in chimps) or a different virus (simian immunodeficiency virus [SIV] or simian/human immunodeficiency virus [SHIV] in monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
136
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 25 publications
(29 reference statements)
3
136
1
1
Order By: Relevance
“…At the forefront of this research is the evaluation of the role of Treg cells in both viral clearance mechanisms and immune-pathology described in chronic HIV infection. An earlier study from our lab demonstrated HIV infection in the BALB/c-DKO-hu mouse model mimicked infection in HIV + patients, namely an increase in viral load followed by a subsequent depletion of CD4 + T cells and an inversion of the CD4 + /CD8 + Tcell ratio in the peripheral blood [123]. Both naïve and memory subsets (CD45RO + and CD45RO − ) of CD4 + T cells were infected in lymphoid organs similar to HIV-infected patients [127].…”
Section: Hiv-1 Pathogenesis In the Humanized Mouse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…At the forefront of this research is the evaluation of the role of Treg cells in both viral clearance mechanisms and immune-pathology described in chronic HIV infection. An earlier study from our lab demonstrated HIV infection in the BALB/c-DKO-hu mouse model mimicked infection in HIV + patients, namely an increase in viral load followed by a subsequent depletion of CD4 + T cells and an inversion of the CD4 + /CD8 + Tcell ratio in the peripheral blood [123]. Both naïve and memory subsets (CD45RO + and CD45RO − ) of CD4 + T cells were infected in lymphoid organs similar to HIV-infected patients [127].…”
Section: Hiv-1 Pathogenesis In the Humanized Mouse Modelmentioning
confidence: 99%
“…Several groups including our own have demonstrated the efficient use of the BALB/c-DKOhu HSC model for HIV infection utilizing either cord-blood or fetal liver CD34 + cells [121][122][123]. Although all groups were able to show infection of HIV (both CCR5-and CXCR4-tropic virus) in peripheral blood, long term viremia, and depletion of CD4 + T-cell populations similar to HIV-infected patients, they were unable to demonstrate appreciable levels of anti-HIV antibody responses.…”
Section: Emerging Humanized Mouse Models For the Study Of Hiv Infectimentioning
confidence: 99%
“…In this context, humanized mouse models that have a closer resemblance to the human immune system could offer great benefits in pre-clinical research by lessening type 1 and type 2 errors made by a wrongful extrapolation of results obtained from common animal models. Humanized mouse models have already been extensively employed in research of cancer and human-specific viruses, such as HIV and herpes (110)(111)(112), however, their use in bacterial pneumonia models is not well established. A humanized bacterial pneumonia model could offer significant advantages over wild type animals.…”
Section: Humanized Modelsmentioning
confidence: 99%
“…Long-term functional engraftment of a human immune system was achieved in immune deficient mice reconstituted with human hematopoietic stem cells (HSC) in divergent genetic backgrounds: NOD/scid-IL-2R␥ c null (NSG), [7][8][9][10] BALB/c-Rag2 Ϫ/Ϫ ␥ c Ϫ/Ϫ (BRG), [11][12][13][14][15] and NOD/ scid mice reconstituted with fetal thymus/liver and HSC (BLT). 16,17 Despite rapid research advances made in these rodent animal models on HIV-1 disease pathobiology, their importance for studies of HIV-1-related complications, including neuroAIDS, have not been explored.…”
mentioning
confidence: 99%